تكاثر سمك السردين المبروم (Valenciennes, 1847) Sardinella aurita في الساحل السوري. - سعد أديب; سليمان يانا (Latakia University Journal -Biological Sciences Series, 2017)
خلال المدة من نيسان 2014 ولغاية آذار 2015 جمعت 410 سمكة سردين مبروم من الساحل السوري، تراوحت أطوالها بين 27-8.1 سم وأوزانها الكلية بين 137.29-6.94 غ لغرض التعرف على بعض الجوانب التكاثرية لسمكة السردين المبروم في الساحل السوري. تصل الذكور والإناث إلى قمة النضج الجنسي بداية شهر حزيران حيث بلغت دالة المناسل (GSI) Gonads Somatic Index أعلى قيمة لها 4.22 للإناث و 5.80 للذكور. وصلت ذكور و إناث السردين المبروم لأول نضج جنسي بطول(17.9 و 18.6 سم على التوالي). ارتفع متوسط الخصوبة المطلقة مع طول الجسم ( ) والوزن ( )، بمتوسط إنتاج بويضات 4876.21±20714.79 وتراوحت الخصوبة النسبية بين242 - 285 بيضة/غرام من وزن السمكة ( المتوسط266.17±21.49 : بويضة/غ). وقد دلت دراسة التوزع التكراري للبيوض على وجود قمة واحدة في منحني التوزع للنوع sardinella aurita وتراوحت اقطار البيوض بين 0.7-0.2 ملم بمتوسط 0.45±0.18ملم. A total of 410 Sardinella aurita Fish , were collected from Syrian coast during the period from April 2014 to March 2015.Total length and weight ranged between 81 – 270 mm, 6.94 –137.29g respectively. The aim of present study was to illustrated some aspects of reproduction biology for Sardinella aurita. . Gonads Somatic Index (G.S.I.) for female and male recorded highest value in early June 4.22 and 5.80 respectively. Male and females round sardinella reach first sexual maturity at total length (17.97 cm and 18.67 cm respectively). Mean absolute fecundity (FA) increased with body length ( ) and weight ( ), with an average of 20714.79 ±4876.21 oocytes produced per spawning female. Relative fecundity (FR) ranged between 242 and 285 oocytes/g of body weight (average: 266.17 ±21.49 oocytes/g). The study on the frequency distribution of eggs diameters revealed the presence of one beak of sardinella aurita. The egg diameters of sardinella aurita ranged between 0.2mm -0.7mm with an average 0.45±0.18 mm.